Common antigens among systemic disease fungi analyzed by two-dimensional immunoelectrophoresis. - Huppert, M (1979)
The interpretation of immunological results in systemic mycoses has been complicated by cross-reactions among specimens from patients with blastomycosis, coccidioidomycosis, and histoplasmosis. The fungal preparations used in these tests evidently contained one or more antigens in common. Two-dimensional immunoelectrophoresis techniques were used to determine the number of antigens contained in several soluble extracts from Blastomyces dermatitidis and Histoplasma capsulatum that were common with those demonstrable in a coccidiodin-anticoccidioidin reference system. A total of 12 and 10 common antigens were found in preparations from B. dermatitidis and H. capsulatum, respectively. In addition, the crude preparations from each species of fungus exhibited some qualitative and quantitative differences in composition of antigens. Use of two-dimensional immunoelectrophoresis for standardization of fungus extracts, for monitoring separation of species-specific antigens, and for testing humoral antibody response should add further refinement to correlations with clinical disease.